Analisis Sektor Unggulan Kota Bontang (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
This study aims to analyze the leading sector of the City Bontang, as well as find out potential sector that can be developed into leading sector in the future. The data used in this study are secondary data in the form of PDRB Bontang and the Province of east Kalimantan, in the period 2013-2017 with constant prices. Data sourced from the Badan Pusat Statistik (BPS) the province of east Kalimantan. The analysis model used is Location Quotient (LQ) and Shift Share.            The results showed that the economic sector included in the Bontang City base sector, namely the Manufacturing Sector and The Busisness Activities Sector. Shift in the economic structure of the Bontang City which resulted in a positive net shift occorred in the Agriculture, Forestry and Fishing Sector, Electricity and Gas Sector, Water Supply, Sewerage Waste Management and Remediation Activities Sector, Construction Sector, Whole Sale and Ratail Trade; Repair of Motor Vehicles and Motorcycle Sector, Trasportation and Strorage Sector, Accommodation and Food Service Activities Sector, Business Activities Sector, Public Administration and Defence; Compulsory Social Security Sector, Education Sector, Human Health and Social Work Activities Sector, and Other Services Activities Sector. The leading sector based on the basis and shift of the economic sector in the city of Bontang is the Business Activities Sector. Sectors that can be developed into leading sectors in the future based on the existing potential in Bontang are the Construction Sector, Education Sector and Agriculture, Forestry and Fishing Sector.